UGT2B17 copy number gain in a large ankylosing spondylitis multiplex family - Uddin, Mohammed (BioMed Central, 2013)
BACKGROUND: The primary objective of this study is to identify novel copy number variations (CNVs) associated with familial ankylosing spondylitis (AS). A customized genome-wide microarray was designed to detect CNVs and applied to a multiplex AS family with six (6) affected family members. CNVs were detected using the built-in DNA analytics aberration detection method-2 (ADM-2) algorithm. Gene enrichment analysis was performed to observe the segregation. Subsequent validation was performed using real time quantitative fluorescence polymerase reaction (QF-PCR). The frequency of copy number variation for the UGT2B17 gene was then performed on two well-defined AS cohorts. Fisher exact test was performed to quantify the association. RESULTS: Our family-based analysis revealed ten gene-enriched CNVs that segregate with all six family members affected with AS. Based on the proposed function and the polymorphic nature of the UGT2B17 gene, the UGT2B17 gene CNV was selected for validation using real time QF-PCR with full concordance. The frequency of two copies of the UGT2B17 gene CNV was 0.41 in the Newfoundland AS cases and 0.35 in the Newfoundland controls (OR = 1.26(0.99-1.59); p < 0.05)), whereas the frequency of two (2) copies of the UGT2B17 gene CNV was 0.40 in the Alberta AS cases and 0.39 in the Alberta controls (OR = 1.05(95% CI: 0.83-1.33); p < 0.71)). CONCLUSIONS: A genome-wide microarray interrogation of a large multiplex AS family revealed segregation of the UGT2B17 gene CNV among all affected family members. The association of the UGT2B17 CNV with AS is particularly interesting given the recent association of this CNV with osteoporosis and the proposed function as it encodes a key enzyme that inhibits androgens. However, two copies of the UGT2B17 gene CNV were only marginally significant in a uniplex AS cohort from Newfoundland but not in a uniplex AS cohort from Alberta.